2020
DOI: 10.5194/essd-2020-57
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Annual 30-meter Dataset for Glacial Lakes in High Mountain Asia from 2008 to 2017

Abstract: Climate change is intensifying glacier melting and lake development in High Mountain Asia (HMA), which could increase glacial lake outburst flood hazards and impact water resource and hydroelectric power management. However, quantification of variability in size and type of glacial lakes at high resolution has been incomplete in HMA. Here, we developed a HMA Glacial Lake Inventory (Hi-MAG) database to characterize the annual coverage of glacial lakes from 2008 20 to 2017 at 30 m resolution using Landsat satell… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Figure 11. Comparison of the mapped supraglacial lakes with the glacial lake inventory of HMA [36], Hi-MAG database [61] and glacial lakes inventory of CPEC [62]. Surprisingly, the Hi-MAG and CPEC inventories have not detected supraglacial lakes on the Baltoro glacier.…”
Section: Mapping Supraglacial Lakes On the Baltoro Glacier And Comparmentioning
confidence: 94%
See 3 more Smart Citations
“…Figure 11. Comparison of the mapped supraglacial lakes with the glacial lake inventory of HMA [36], Hi-MAG database [61] and glacial lakes inventory of CPEC [62]. Surprisingly, the Hi-MAG and CPEC inventories have not detected supraglacial lakes on the Baltoro glacier.…”
Section: Mapping Supraglacial Lakes On the Baltoro Glacier And Comparmentioning
confidence: 94%
“…The sizes of the supraglacial lakes on the Baltoro glacier mapped using PlanetScope imagery of different dates are given in Table 3. We then used the following inventories for comparison: (1) glacial lakes inventory of High Mountain Asia [36], (2) A dataset of glacial lakes in High Mountain Asia (Hi-MAG) from 2008 to 2017 [61] and (3) glacial lakes in the China-Pakistan Economic Corridor (CPEC) [62]. These three inventories have been derived from Landsat-8 imagery (recent years).…”
Section: Mapping Supraglacial Lakes On the Baltoro Glacier And Comparmentioning
confidence: 99%
See 2 more Smart Citations
“…We compared our lakes and pond extents with two existing glacial lakes databases constructed from the same year (2015 Landsat): the HMA v.1 lake dataset, derived using a normalized difference water index (Shugar, 2020b) and HI-MAG constructed using a modified NDWI and manual corrections (Chen et al, 2020). A comparison with other global databases such as the Global Surface Water (GSW) (Pekel et al, 2016) was not undertaken here, as this has already been shown to underestimate the water occurrence over most of the Himalaya by Chen et al (2020). With regards to HMA v1 and HI-MAG datasets, Figure 13 shows that the lake outlines obtained from spectral unmixing in this study are outperforming both of the existing databases.…”
Section: Fig 13 Herementioning
confidence: 99%